(untitled) (Swiss Medical Weekly, 2013)
Cells reside in mechanically rich and dynamic microenvironments, and the complex interplay between mechanics and biology is widely acknowledged. Recent research has yielded insights linking the mechanobiology of cells, human physiology, and pathophysiology. In particular, we have learned of the cell’s astounding ability to sense and respond to its mechanical microenvironment. This seemingly innate behaviour of the cell has driven efforts to characterise precisely the cellular behaviour from a mechanical viewpoint. Here we present an overview of technologies used to probe cell mechanical and material properties, how they have led to the discovery of seemingly strange cellular mechanical behaviours, and their influential role in health and disease, including asthma, cancer, and glaucoma. The properties reviewed here have implications in physiology and pathology and raise questions that will fuel research opportunities for years to come.